Neutralization of a Low Molecular Weight Heparin (LHN-1) and Conventional Heparin by Protamine Sulfate in Rats - Diness, V; Østergaard, P B (Thrombosis and Haemostasis, 1986)
The neutralization of a low molecular weight heparin (LHN-1) and conventional heparin (CH) by protamine sulfate has been studied in vitro and in vivo. In vitro, the APTT activity of CH was completely neutralized in parallel with the anti-Xa activity. The APTT activity of LHN-1 was almost completely neutralized in a way similar to the APTT activity of CH, whereas the anti-Xa activity of LHN-1 was only partially neutralized.In vivo, CH 3 mg/kg and LHN-1 7.2 mg/kg was given intravenously in rats. The APTT and anti-Xa activities, after neutralization by protamine sulfate in vivo, were similar to the results in vitro. In CH treated rats no haemorrhagic effect in the rat tail bleeding test and no antithrombotic effect in the rat stasis model was found at a protamine sulfate to heparin ratio of about 1, which neutralized APTT and anti-Xa activities. In LHN-1 treated rats the haemorrhagic effect was neutralized when APTT was close to normal whereas higher doses of protamine sulfate were required for neutralization of the antithrombotic effect. This probably reflects the fact that in most experimental models higher doses of heparin are needed to induce bleeding than to prevent thrombus formation. Our results demonstrate that even if complete neutralization of APTT and anti-Xa activities were not seen in LHN-1 treated rats, the in vivo effects of LHN-1 could be neutralized as efficiently as those of conventional heparin. The large fall in blood pressure caused by high doses of protamine sulfate alone was prevented by the prior injection of LHN-1.
Keywords: LMW heparin; Protamine sulfate